2017
DOI: 10.1016/j.cell.2017.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Multi-invasions Are Recombination Byproducts that Induce Chromosomal Rearrangements

Abstract: SUMMARY Inaccurate repair of broken chromosomes generates structural variants that can fuel evolution and inflict pathology. We describe a novel rearrangement mechanism in which translocation between intact chromosomes is induced by a lesion on a third chromosome. This multi-invasion-induced rearrangement (MIR) stems from a homologous recombination byproduct, where a broken DNA end simultaneously invades two intact donors. No homology is required between the donors, and the intervening sequence from the invadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
189
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(200 citation statements)
references
References 75 publications
11
189
0
Order By: Relevance
“…This possibly reflects a stabilisation of the duplex by the number of paired bases but could also result from the fact that the recombination filament is able to simultaneously bind multiple noncontiguous sequences. This has been observed in vitro for the RecA filament (Forget and Kowalczykowski 2012) and 1 3 more recently in vivo in S. cerevisiae (Piazza et al 2017). Although these observations explain that a certain amount of resected DNA is required for efficient homology search in vivo, the fact that slowing down resection can increase recombination efficiency at subtelomeric and some intrachromosomic DSBs (Lee et al 2016;Batté et al 2017) suggests that too much resection can also limit HR.…”
Section: Resection a Ticking Clock For Homology Search?mentioning
confidence: 87%
“…This possibly reflects a stabilisation of the duplex by the number of paired bases but could also result from the fact that the recombination filament is able to simultaneously bind multiple noncontiguous sequences. This has been observed in vitro for the RecA filament (Forget and Kowalczykowski 2012) and 1 3 more recently in vivo in S. cerevisiae (Piazza et al 2017). Although these observations explain that a certain amount of resected DNA is required for efficient homology search in vivo, the fact that slowing down resection can increase recombination efficiency at subtelomeric and some intrachromosomic DSBs (Lee et al 2016;Batté et al 2017) suggests that too much resection can also limit HR.…”
Section: Resection a Ticking Clock For Homology Search?mentioning
confidence: 87%
“…Forget and Kowalczykowski concluded that an efficient homology search is three-dimensional and that the RecA filament could “brachiate” - the way apes transfer from branch to branch - holding on to one place while reaching out to find another nearby contact. Multiple contacts of a Rad51 filament have also been inferred from in vivo experiments with budding yeast, by studying complex rearrangements caused by a single DSB [52]. …”
Section: How Long Does the Search For Homology Take?mentioning
confidence: 99%
“…The observed effects of different parental and recombinant classes amongst progeny having undergone a gene conversion event can be explained by envisioning a DSB 5' or 3' of a point mutation leading to a recombination intermediate (D-loop, Holliday junction), which will then be processed immediately at the break site, or ends up somewhat removed from the initial break site by multiple consecutive invasion steps, by branch migration, or both [40][41][42] . The genetic makeup of the progeny is, therefore, a compound result of processing distinct recombination intermediates in different ways.…”
Section: Mutsα and Mutlα Are Strong Negative Modulators Of Recombinatmentioning
confidence: 99%